A Study of the Clinical Profile of Patients with Upper Gastrointestinal Bleed and Utility of Rockall Scoring in these Patients at a Tertiary Healthcare Setup - Sanjay Mundhe 1, Nagnath Redewad 1, Dhananjay Ogale 1, Khushmi Shah 1and Rohidas Borse1 (Walawalkar International Medical Journal, 2022)
Background: Upper gastrointestinal bleed (UGI Bleed) is common emergencies contributing to hospitalization and associated morbidity and mortality. Numerous scoring systems have been designed to assess risk factors for morbid outcome. Aim and Objectives: To study demographic and clinical profile of patients with UGI bleed. To study the aetiology of patients with UGI bleed. To study utility of Rockall system and correlate severity of bleed with outcome. Material and Methods: This observational cross- sectional study was carried out at a tertiary care hospital. Study was carried out on patients presenting with UGI bleed and who consented to participate. Ethical committee approval was obtained. Relevant data of eligible patients over two years was collected. Data collected was compiled using excel sheet and analysed with Graph Pad Prism Version V. Results reported in terms of mean, percentages and p-value. P-value <0.05 was considered statistically significant. Results: Mean age was 44.73 years with range of 18-82 years. Males were 72% of and females 28%. Majority, 54% presented with hematemesis, 24% had melena, while 22% had both. Alcohol intake was found in 84 (56%) patients. 54.6% patients had variceal bleed and 45.3% had non-variceal bleed. Eleven patients (15.37%) with moderate category had re-bleeding while 1(50%) had re-bleed in severe category. There was no mortality amongst low and moderate categories and 50% mortality in severe category. Conclusion: UGI bleed commonly presents as hematemesis, seen in middle-aged males with significant alcohol intake. Higher Rockall score was associated with transfusion requirement, occurrences of rebleed and mortality.